Sovereignty as new beginnings: Action beyond the liberal subject, among undercover police investigators in Europe, for example. (September 2022) - Feldman, Gregory
This article argues that Schmitt's "state of exception" is only one expression of the deeper sovereign phenomenon, specifically the human capacity to inaugurate new beginnings in shared space. Sovereign action thus includes anything from Schmitt's vertically-imposed state of exception, which eliminates political subjecthood, to the thrill of horizontally-arranged movements, which enable it. To make this argument, the article foregoes the idea of the bounded, internally coherent liberal subject in favor of a relational subject, who is both internally divided and inherently tied to others. The subject's instability and relationality make new beginnings possible and renders sovereign action promising, even if risky. An unexpected example of this fuller view of sovereignty appears in an undercover police team in southern Europe that investigates global human smuggling and trafficking rings. Based on extensive ethnographic research, this article shows how they often act on their own ethical judgments, reached by considering the standpoints of people tied to their investigations, rather than through obedience to law, policy, or superior command. Acting outside constitutional order, these investigators, (re)constitute themselves as particular persons through their joint actions and simultaneously constitute modest sovereign spaces, however tentatively.